2021
DOI: 10.1111/ppl.13477
|View full text |Cite
|
Sign up to set email alerts
|

Differential protein abundance of vetiver grass in response to acid mine drainage

Abstract: Acid mine drainage (AMD) is an acidic and metalliferous discharge that imposes oxidative stress on living things through bioaccumulation and physical exposure. The abandoned Tab-Simco mining site of Southern Illinois generates highly acidic AMD with elevated sulfate (SO 4 2À ) and various metals. Vetiver grass (Chrysopogon zizanioides) is effective for the remediation of Tab-Simco AMD at both mesocosm and microcosm levels over extended periods. In this study, we conducted a proteomic investigation of vetiver s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…In general, the Marykies cultivar responded better than the Royal across the treatments. This could be attributed to differences in the physiological response of the two cultivars as impacted by their molecular properties under AMD environment 54 . The study conducted by 55 also indicated that different plants respond differently in the synthesis of proteins that could play a crucial role in their adaptation and survival under AMD conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the Marykies cultivar responded better than the Royal across the treatments. This could be attributed to differences in the physiological response of the two cultivars as impacted by their molecular properties under AMD environment 54 . The study conducted by 55 also indicated that different plants respond differently in the synthesis of proteins that could play a crucial role in their adaptation and survival under AMD conditions.…”
Section: Resultsmentioning
confidence: 99%